Comparison of the Acute Effects of Different Pacing Sites on Cardiac Synchrony and Contraction Using Speckle-Tracking Echocardiography - Xie, Huilin; Chen, Xueying; Wang, Yanan; Cheng, Yufei; Zhao, Yingjie; Liu, Yang; Liu, Yu; Ge, Zhenyi; Chen, Haiyan; Shu, Xianhong (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardiac pacing in patients with bradyarrhythmia may employ variable pacing sites, which may have different effects on cardiac function. left bundle branch pacing (LBBP) is a new physiological pacing modality, and the acute outcomes on cardiac mechanical synchrony during LBBP remain uncertain. We evaluated the acute effects of four pacing sites on cardiac synchrony and contraction using speckle-tracking echocardiography, and comparisons among four different pacing sites were rare. Methods: We enrolled 21 patients with atrioventricular block or sick sinus syndrome who each sequentially underwent acute pacing protocols, including right ventricular apical pacing (RVAP), right ventricular outflow tract pacing (RVOP), His bundle pacing (HBP), and left bundle branch pacing (LBBP). Electrocardiograms and echocardiograms were recorded at baseline and during pacing. The interventricular mechanical delay (IVMD), the standard deviation of the times to longitudinal peak strain during 17 segments (PSD), and the Yu index were used to evaluate ventricular mechanical synchrony. Layer-specific strain was computed using two-dimensional speckle tracking technique to provide in-depth details about ventricular synchrony and function. Results: Left ventricular ejection fraction (LVEF) and tricuspid annulus plane systolic excursion (TAPSE) were significantly decreased during RVAP and RVOP but were not significantly different during HBP and LBBP compared with baseline. RVAP and RVOP significantly prolonged QRS duration, whereas HBP and LBBP showed non-significant effects. IVMD and PSD were significantly increased during RVAP but were not significantly different during RVOP, HBP, or LBBP. LBBP resulted in a significant improvement in the IVMD and Yu index compared with RVAP. No significant differences in mechanical synchrony were found between HBP and LBBP. Conclusion: Among these pacing modalities, RVAP has a negative acute impact on cardiac synchrony and contraction. HBP and LBBP best preserve physiological cardiac synchrony and function.